Resources for Teaching Mindfulness An International Handbook - McCown, Donald; Reibel, Diane; Micozzi, Marc S. (Springer International Publishing : Imprint: Springer, 2016)
This master-class-in-a-book is designed to guide teachers of mindfulness-based interventions (MBI) in continuing to develop more competence while raising global standards of practice and pedagogy. Starting with the central yet elusive concept of stewardship, it then expands upon the core components of MBI pedagogy. A series of reflective essays by MBI teachers from around the world foregrounds differences and challenges in meeting participants "where they are." Such reflections are both inspiring and thought-provoking for teachers -wherever they are. The book also provides practical guidance and tools for adjusting teaching style and content for special populations, from chronic pain patients to trauma survivors, from health care professionals to clergy, and including many others. Detailed scripts and practices, ready to adopt and adapt, offer opportunities to explore new directions in the classroom, and to continue the life-long development of the teacher. Included in the coverage: • Deepening teachers' skills of guidance of meditation practices • Insights into the essential practice of inquiry and dialogue with participants • New practices that allow participants to explore mindfulness together in a spoken encounter • How to keep up with, review, and make clear to participants the range of scientific evidence supporting the MBIs The breadth of practical insights and hands-on strategies makes Resources for Teaching Mindfulness a unique developmental asset for a wide range of practitioners around the world. Among those who will benefit are physicians and other medical practitioners, health and clinical psychologists, marriage and family therapists, nurses, clinical social workers, physical and occupational therapists, health educators, and organizational development specialists. "A deep, supportive, and challenging dive into the art of teaching mindfulness, including the science of it, in the form of MBSR and other mindfulness-based interventions. Highly experienced contributors offer a cornucopia of inspiring, instrumental, and non-instrumental perspectives on the multi-dimensional topology of the classroom in vastly different contexts and cultures. Of particular note is the intimacy of one's own embodied sharing and exploring of the practice with others as the instructor - with the welcome mat for what arrives within us and between us firmly rolled out in not-knowing, coupled with deep listening, creativity, imagination, daring, and caring." Jon Kabat-Zinn, Founder of MBSR, Author of Full Catastrophe Living and Coming to Our Senses .